ANALISIS STRUKTUR SATUA I DURMA - I Ketut Madja (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
In literary works, in general, discuss the unity of the elements in it. These elements are seen as forming the literary work itself, both in relation to other elements and the overall framework contained in the literary work. Likewise with satua (story) I Durma as a literary work, it cannot be separated from the elements that make it up, such as how the plot or plot, characters and characterizations are, so that it can be said to be a satua (story).Setrukur aims to reveal and explain carefully and thoroughly, in detail and as deep as possible the linkages and interconnections of all elements and aspects of literary works that together produce a comprehensive meaning. For every literary researcher, analysis or study of the structure of the literary work to be studied from anywhere is also a priority task.